Gonadal dysfunctions in Beta Thalassemia Major Adults in association with anemia and iron overload - Mousa, Nada Mostafa; Sliem , Hamdy Ahmed; Rashad, Nermeen Mohammed; Mossad, Ahmed Mohamed; Greash, Mohamed Ahmed (Journal of Neonatal Surgery, 2025)
Background: Endocrine dysfunctions, particularly hypogonadism, are among the most common complications in adults with β-thalassemia major (BTM), significantly impairing quality of life. Objective: To evaluate the effect of anemia and iron overload on gonadal dysfunction in Beta Thalassemia Major Adults in Suez Canal University hospitals Methods: A cross-sectional observational study was conducted at the Endocrinology and Hematology clinics of Suez Canal University Hospital. Sixty participants were divided equally into three groups: (1) BTM patients with gonadal dysfunction, (2) BTM patients without gonadal dysfunction, (both aged more than 18 years) and (3) Age - matched healthy control group. Gondal dysfunction assessed by medical history and lab evaluation, complete blood count and serum ferritin levels was done. Results: Both thalassemia groups showed markedly lower hemoglobin levels compared to the control group, The difference in anemia between thalassemia patients with and without gonadal dysfunctions was not statistically significant (p = 0.174). Serum ferritin was extremely elevated in both thalassemia groups compared to controls, reflecting iron overload, but no statistically significant difference in ferritin levels between thalassemia patients with and without gonadal dysfunctions. (p = 0.989). Conclusion: Hemoglobin level and serum ferritin cannot be used as sole predictors for gonadal dysfunctions in β-thalassemia major (BTM) adults